Spatial-Temporal Analysis of Solar Irradiation and COVID-19 Cases in Jakarta 2020 - Saputra, Yoerdy Agusmal; Susanna, Dewi (Kesmas, 2021)
To date, coronavirus disease 2019 (COVID-19) is still a threat to public health systems around the world. As of July 25, 2021, the numbers were still increasing in most countries, and the total confirmed cases reached 194,582,750 with 4,171,672 deaths (CFR 2.1%). In Indonesia, 3,166,505 cases were reported with 83,279 deaths (CFR 2.7%) in all provinces and dominated by cases from Jakarta. Therefore, this study aimed to find a correlation and the duration of solar radiation exposure spatially on the pattern of COVID-19 cases. An ecological design was used based on time and place with the integration of geographic information systems and statistical techniques. The correlation test results between solar radiation exposure and COVID-19 cases in Jakarta showed a significant relationship (p = 0.000) with a strong closeness and positive pattern (r = 0.666). Furthermore, the spatial map overlaying solar radiation exposure and COVID-19 cases showed urban villages with high radiation tend to increase in cases earlier than areas with moderate and low. The differences in geographical and temporal conditions are a concern for the Provincial Health Office. This can be a consideration in strengthening more specific prevention and control programs according to the risk level and characteristics of each region.